Regionalism after regionalisation : Spain, France and the United Kingdom - Schrijver, F. J. (Frans J.) (UvA Proefschriften Ser., 2006)
Concentrating on three countries, Spain, France and the United Kingdom, and three regional case studies of Galicia, Brittany and Wales, this book offers an analysis of the development of political regionalism after regionalisation.